Towards human resource development at Hanoi Open University - Hong Thi Thuy Nguyen (AAOU Journal, 2018)
Purpose - The purpose of this paper is to investigate the roles of human resource development (HRD) in open universities. The study also intends to assess the current situation of HRD at Hanoi Open University (HOU) with an end view of proposing some suggested recommendations to enhance HRD to improve the training quality and effectiveness at HOU. Design/methodology/approach - The study’s first two parts refer to HRD’s role in open universities. The third one summarizes the existing research literature on HRD used as theoretical base for the author to evaluate the current HRD at HOU in the fourth part. The fifth part involves the methodology to gather the data on HRD practices at HOU while the next two important parts deal with the study’s findings and recommendations for better HRD at HOU. The final part summaries the study’s main points. Referring methodology, the survey data were analyzed through frequency, percentage and weighted mean as statistical tools. Findings - The study’s findings show that HRD practices at HOU are not as effective as expected in terms of human resource quality, human resource structure and human resource management. There is a shortage of full-time well-qualified employees, inadequate and imbalance working positions, and un-synchronous, fragmented personnel management. Originality/value - The study’s values are not only useful for building policies on HRD but also for developing strategies to train and foster capable and adequate staff in open universities’ academic environment and in HOU as well.